(untitled) (International Conference on Computers in Education, 2013)
With the advance of technology, the price drop and the increasing reliance of personal computers showed possibilities on transforming our current education. As mentioned in Bloom’s 2-sigma problem (Bloom, 1984), one-to-one classroom learning proved a significant learning outcome compared to the conventional. Therefore, with the assist of technology, applying 1:1 learning in the regular practice might be the ultimate goal for the educational transform. In this study, we explored the experiences and showed encountered problems for 1:1 learning in Taiwan. The experience was categorized into users and technology, followed by the analysis of criteria that based on empirical observations. As a result, the observation provided a guideline for the technology readiness, which consisted of the perception of users (teachers & administrators, students & parents) and the stability of pedagogical and hardware integration (pedagogy/software and devices). The result of this study also suggested that further attention should be addressed on the hardware infrastructure and the teacher’s professional training, because there were over 50% of encountered problems that were mainly the problems for stability of computer hardware (54.41%). Most problems encountered by teachers & administrators could be solved by effective professional trainings and flexible school assessments (31.00%). Nevertheless, neither students nor parents showed a high participation ratio in this study (14.59%).